Visual inspection for cervical câncer screening - Galvane, Janice O.; Martins, Cecília M. Roteli; Tadini, Valdir (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Objetive: To evaluate the results of acetic acid application, with naked eye inspection (VIA), as accessory test for cervical cancer, in public primary-care clinic in São Paulo city (East zone). Methods: cross-sectional study with 150 voluntary women in the Reference Center Vila Guarani. Pap smears and acetic- acid 5% application in the cervix were done concurrently. The abnormal cases by Pap smear and VIA were refereed to colposcopy with biopsy as indicated. The normal cases by VIA with abnormal Pap smear were also refereed to colposcopy.. Sensitivity, specificity and preditive value positive and negative were calculated with 95% confidence interval.. Results: in this preliminary study, the visual inspection showed improvement in cervical intraepithelial neoplasia screening.. In this sample we found same results as previous studies. Sensitivity was 79%. specificity was 46% and the positive preditive value was57%. Conclusion: the high sensitivity of VIA shows that the test could be valuable as Pap smear accessory detection of precancerous lesions from the cervix. Our findings showed that VIA could be a great aid in the triage of cases that should be refereed to colposcopy and biopsy in poorly resourced locations as well in urban areas where the Pap smear is available.